Penentuan Waktu Standar dam Jumlah Tenaga Kerja Optimal pada Bagian Winding Primercurrent Transformer (Travo Arus) - Ismail, Mohammad Farid; Rahayuningsih, Sri; Komari, Ana (Universitas Kadiri, 2020)
In the production process using this work sampling method aims to determine whether a job is fast or not so that workers work in typical conditions that are needed in the production of primary current transformer winding based on standard time. The sampling method was developed based on the low probability. By using a degree of the confidence level of 95% and a level of accuracy of 5%, and the adjustment factor with the westing house method. The results of this study indicate the standard time required by worker 1 to complete the work is 128.4 minutes/unit; worker 2 is 125.7 minutes/unit, worker 3 is 121.9 minutes/unit and standard time of worker 4 is 123.3 minutes/unit. And the optimal number of workers that should be employed is 5.1 people, while the number of workers available in the primary winding current transformers is 4 people, so there is a need to add 1 new workforce so that the products produced according to the specified time. It is also known that the average productivity of all operators is 89.37% with the percentage of idle (idle time) of 10.62%.Kegiatan dalam proses produksi divisi winding primer current transformer dilakukan penelitian yang berkaitan dengan produktivitas menggunakan metode work sampling. Didalam metode tersebut, digunakan tingkat kepercayaan sebesar 95% dan tingkat ketelitian sebesar 5% dengan penyesuaian yang menggunakan metode westing house. Didalam perhitungannya dihasilkan nilai standar pada pekerja 1 ketika selesai tiap project dengan waktu sebesar 128,4 menit/ unit, kemudian pada pekerja 2 sebesar 125,7 menit/ unit, pada pekerja 3 sebesar 121,9 menit/ unit dan untuk pekerja 4 dapat menyelesaikan per project winding current transformer sebesar 123,3 menit/ unit. Dalam penggunaan tenaga kerja yang optimal didapat hasil bahwa dibutuhkan 5,1 atau 5 orang yang digunakan untuk melakukan proses produksi. Sehingga, pada awalnya ada 4 pekerja maka harus ditambah sebanyak 1 orang agar produk yang dihasilkan sesuai waktu yang sudah ditentukan. Disini diketahui juga produktivitas rata-rata semua operator sebesar 89,37 % dengan prosentase idle (waktu menganggur) sebesar 10,62 %.Â